ENHANCING LANGUAGE STUDENTS AUTONOMYTHROUGH PERFORMING WORD-FORMATION PROCESSES A TERM PAPER - عبد الجبار كمال رشيد, سندس (Al-Adab Journal, 2018)
A man's use of words is commonly taken as a measure of his knowledge and even of his intelligence. Creativity is one of the distinctive properties of human language, it is the ability to produce and understand new forms in a language. Creativity is mostly crystallized when it comes to words formation in general and internet created words in particular. It is apparent in speakers’ lexical knowledge as well , where new lexes are appended to our mental repertoire constantly. The aim of this study is to determine whether performing word formation processes supports EFL college students autonomy and to identify the most vital word formation processes activated on internet language . The research is an experimental one where a sample of (30) students of 2nd year students at the College of Education / Ibn-Rushd for the academic year 2014-2015 randomly selected to take a pre-test on morphology in general and word formation processes characterized by affixation in particular to identify the formed words and to derive new words mainly by the process of derivation being the most focused process in the curriculum. After three months course teaching of word formation processes highlighted mostly by the most common processesDeveloped by internet language , a post-test is administered. Finally, in order to capture the probable significance of performing these processes on students’ autonomy, a(Mann-Whitney U test ) is used. The results come to reject the null hypothesis, and prove positively the enhancement achieved through learning and performing these processes especially when enriched by up-to-date internet derivations and creativity.